Use of a blood test incorporating age, sex, and gene expression influences medical decision-making in the evaluation of women presenting with symptoms suggestive of obstructive coronary artery disease: summary results from two ambulatory care studies in primary care. Issue 11 (November 2015) - Ladapo, Joseph A.; Herman, Lee; Weiner, Bonnie H.; Rhees, Brian; Castle, Lon; Monane, Mark; McPherson, John A.
Abstract: Objective: Clinicians need better approaches to evaluating women at midlife and beyond who present to primary care with chest pain and related symptoms. A previously validated blood-based test, which includes age, sex, and gene expression levels, showed a 96% negative predictive value for determining an individual's current likelihood of having obstructive coronary artery disease (CAD) in a combined population of men and women. We hypothesized that age/sex/gene expression score (ASGES) would be incorporated into medical decision-making and would influence the rate of further cardiac evaluation. Methods: An aggregate analysis of female cohorts from the Investigation of a Molecular Personalized Coronary Gene Expression Test on Primary Care Practice Pattern (IMPACT-PCP; NCT01594411) and REGISTRY I (NCT01557855) studies was conducted. Data on 320 women presenting with stable symptoms suggestive of obstructive CAD and undergoing ASGES testing (from 16 primary care providers in geographically diverse sites) were pooled. The primary outcome of this analysis was the association between ASGES and referrals for further cardiac evaluation. Results: The mean participant age was 57.8 years, and the mean ASGES (predefined as low [ASGES ⩽15] or elevated [ASGES >15]) was 10.3. The referral rate for further cardiac evaluation was 4.0% (10 of 248) for women with low ASGES versus 83.3% (60 of 72) for women with elevated ASGES, with an overall follow-up major adverse cardiac event/revascularization rate of 1.2%. After adjustment for clinical covariates, women with low ASGES were significantly less likely to be referred for further cardiac evaluation (odds ratio, 0.013; P  < 0.0001). Conclusions: ASGES can be incorporated into medical decision-making to help primary care providers rule out obstructive CAD among symptomatic women who are unlikely to benefit from further cardiac testing.